2022
DOI: 10.1007/s10549-021-06449-4
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib alone and in combination with vinorelbine or paclitaxel, in patients with HER2-positive breast cancer who failed or progressed on prior trastuzumab and/or lapatinib (LUX-Breast 2): an open-label, multicenter, phase II trial

Abstract: Purpose Resistance to HER2 (ErbB2)-targeted therapy may be mediated by other members of the ErbB family. We investigated the efficacy and safety of the irreversible ErbB family blocker, afatinib, alone as first-line therapy in the advanced setting and in combination with vinorelbine or paclitaxel for those who progressed on afatinib monotherapy, in female patients with metastatic breast cancer who had failed or progressed on prior HER2-targeted therapy in the early disease setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The investigations of AFT treatment in BRCA are undergoing. In an open-label, multicenter, and phase II clinical trial, Hickish et al (74) reported that for metastatic BRCA patients whose prior HER2-targeted therapy had undesirably failed, AFT alone and combined with paclitaxel or vinorelbine could enhance the objective response. Our data demonstrated AFT may have a good therapeutic effect on TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…The investigations of AFT treatment in BRCA are undergoing. In an open-label, multicenter, and phase II clinical trial, Hickish et al (74) reported that for metastatic BRCA patients whose prior HER2-targeted therapy had undesirably failed, AFT alone and combined with paclitaxel or vinorelbine could enhance the objective response. Our data demonstrated AFT may have a good therapeutic effect on TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Afatinib is a pan-HER TKI that is irreversible and has a strong affinity for EGFR, A phase III trial using afatinib to treat HER2 was proposed to early stop recruiting by an independent data tracking group ( Hurvitz et al, 2014 ; Wind et al, 2017 ). In the initial analysis of open-label, phase III LUX-Breast 1 trial the median PFS for the afatinib and trastuzumab groups was 5 months and 6 months, respectively (HR Z 1.10; 95% CI: 0.86–1.41; PZ 0.43) ( Hurvitz et al, 2014 ; Wind et al, 2017 ; Hickish et al, 2022 ). Five percent of afatinib patients and 3% of trastuzumab patients had dosage decreases because of AEs.…”
Section: Tyrosine Kinase Inhibitor Therapy For Her2+ Mbcmentioning
confidence: 99%
“…Five percent of afatinib patients and 3% of trastuzumab patients had dosage decreases because of AEs. Treatment was required for 15% of patients in the afatinib arm and 7% of participants in the trastuzumab arm ( Hurvitz et al, 2014 ; Wind et al, 2017 ; Hickish et al, 2022 ). One-quarter of patients in the afatinib group had their dose reduced because of diarrhea, rash, nausea, tiredness, and stomatitis were the most common AEs of any grade.…”
Section: Tyrosine Kinase Inhibitor Therapy For Her2+ Mbcmentioning
confidence: 99%
See 1 more Smart Citation
“…Afatinib is a promising backbone combination partner for a variety of novel regimens with multiple indications. Among these regimens, afatinib is being used in combination with vinorelbine in patients with breast or lung cancer 6,7 . Although we previously reported that afatinib plus vinorelbine had synergistic effect on various lung cancer cells, 8 clinical trials of the two drugs in NSCLC have not been conducted, possibly due to the availability of other more tolerable therapies 5 .…”
Section: Introductionmentioning
confidence: 99%